The Emerald International Handbook of Technology-Facilitated Violence and Abuse 2021
DOI: 10.1108/978-1-83982-848-520211032
|View full text |Cite
|
Sign up to set email alerts
|

Technology as Both a Facilitator of and Response to Youth Intimate Partner Violence: Perspectives from Advocates in the Global-South

Abstract: Much of the research on intimate partner violence focuses on adults, and little of it emanates from the Global-South. The study reported upon in this chapter is aimed at addressing these gaps. Adopting a Southern Feminist Framework, it discusses findings from interviews with Brasilian and Australian advocates working on prevention of youth IPV. Participants from both countries noted disturbing instances of digital coercive control among the youth with whom they work, as well as underlying factors such as gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It is important to note that although the cybersphere could be an inclusive and interactive environment for mental health intervention development and distribution, it is often haunted by issues ranging from high dependence on basic infrastructure (e.g., broadband access) and cybercrimes (e.g., cyberbullying and cyberstalking) to social media addiction [ 59 , 60 , 61 , 62 , 63 ]. Studies found that privacy and security issues inherent to technological devices and platforms could influence victims’ appreciation and utilization of technology-based mental health interventions [ 62 ], not to mention that in cybersphere, damage related to privacy and data-handling breaches could be extremely difficult to estimate and/or contain.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that although the cybersphere could be an inclusive and interactive environment for mental health intervention development and distribution, it is often haunted by issues ranging from high dependence on basic infrastructure (e.g., broadband access) and cybercrimes (e.g., cyberbullying and cyberstalking) to social media addiction [ 59 , 60 , 61 , 62 , 63 ]. Studies found that privacy and security issues inherent to technological devices and platforms could influence victims’ appreciation and utilization of technology-based mental health interventions [ 62 ], not to mention that in cybersphere, damage related to privacy and data-handling breaches could be extremely difficult to estimate and/or contain.…”
Section: Discussionmentioning
confidence: 99%
“…In the world, around 16 million teenagers give birth each year, with 95% of them coming from upcoming nations. Nearly a quarter of girls between the ages of 15 and 19 are married (LMICs) [6]. Trends in an increased rate of unmarriages do not point to a reduction in the age at which youths first engage in sexual activity; instead, there is a need to improve access to SRH knowledge, services, and skills so that people can learn more about sexuality, avoid unintended pregnancies, and stop sexually transmitted diseases [7].…”
Section: Introductionmentioning
confidence: 99%